Aortic Bifurcation and Its Relationship to the Lumbosacral Spine: Insights from MRI Imaging - Sapkota, Diwas; Paudel, Keshab; Sapkota, Dilip; Baral, Ekta (Journal of Bharatpur Hospital, 2025)
Background The anatomical relationship of the aortic bifurcation to the lumbar vertebrae is crucial in vascular, orthopedic and neurosurgical procedures. Variations in the aortic bifurcation location can impact vascular surgeries, lumbar spine interventions and diagnostic imaging interpretations. However, most anatomical data are based on Western populations and there is a lack of MRI-based studies focusing on the Nepali population. Given the rising burden of vascular diseases and spinal disorders in Nepal, understanding these anatomical variations is essential for improving clinical outcomes. This study aims to use MRI to determine the level of aortic bifurcation in nepali population. MethodsA cross-sectional study was conducted in the Department of Radiology, Bharatpur Hospital from September 2024 to March 2025. 200 patients presenting for MRI above 20 years of age in the radiology department were taken as cases. The level of the aortic bifurcation was analyzed using axial and sagittal midline MRI images. These positions were documented in relation to either the upper , mid or lower level of the nearby vertebral body or the adjacent intervertebral disc space.ResultsOut of 200 patients aortic bifurcation was seen in most cases at the level of L4 vertebral body. Conclusions In the current study, the aortic bifurcation is predominantly observed at the level of the L4 vertebra, aligning with findings from most of the earlier research.